Processos de digitalização: escolhas eficientes para difusão de acervos e arquivos - Pereira, Márcio André Ferreira (2019)
This paper researches options to help the preservation and diffusion of collections and archives linked to cultural issues such as museums, institutes and others that seek as a means of preserving and expanding the diffusion of information technologies - ensuring their preservation in digital format. It is concerned with technological obsolescence in this process, which may lead to information loss. The research is qualitative and bibliographic with field research using the data collection instruments of the case study Projeto Museu de Rua. For bibliographic reference the researches and publications of the main thinkers were used to which stands out the professor Dr. Ingrid Hötte Ambrogi, Acacia Maria Maduro Hagen, Jose Maria Jardim, Kenneth and Jane Laudon, Lev Manovich, Michael Pollak, Miguel Ferreira, Pierre Nora , Sylvia Caiuby Novaes, G. Somasundaram, Alok Shrivastava and EMC Education Services. Many challenges were found in the Museu de Rua Case Study such as cataloging and processing of images, setting up the best cataloging card to be implemented in BibLivre and the availability of infrastructure offered by Mackenzie. With the submission of the new project Museu de Rua do Bexiga, and, if approved, it is expected to contribute to the digitization and availability of this collection to the community of Bexiga